Implementation of Multicultural Education Strategies in Fostering Tolerance and Intercultural Interaction in Senior High Schools: A Case Study - Firmansyah, Haris; Sastra Atmaja, Thomy; Wiyono, Hadi (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
Multicultural education is a crucial strategy for fostering tolerance and intercultural interaction within school environments, particularly in highly diverse regions such as Singkawang City. This study aimed to identify the strategies employed by teachers to integrate multicultural education into the curriculum and classroom practices at the senior high school level, analyze the supporting and inhibiting factors in its implementation, and evaluate its impact on students’ attitudes toward diversity, tolerance, and cross-cultural engagement. Employing a qualitative approach with a case study method, this research was conducted in three senior high schools in Singkawang. Data were collected through semi-structured interviews, participatory observations, and document analysis. The data analysis technique followed the interactive model of Miles, Huberman, and Saldana, encompassing data condensation, data display, and conclusion drawing. The findings revealed that teachers applied three main strategies: curriculum integration based on local wisdom, the implementation of participatory learning methods, and the use of multicultural digital and visual media. Key supporting factors included principal commitment, regional policy support, and a socially pluralistic context. However, challenges such as limited teacher training, a lack of inclusive teaching materials, and unstructured program sustainability remained significant. These strategies have been shown to enhance students’ multicultural awareness, cross-identity interaction skills, and empathy. The study recommends strengthening context-based teacher training, developing relevant learning resources, and engaging local communities to support the sustainable implementation of multicultural education.